Pengaruh Word of Mouth Terhadap Citra Merek Serta Dampaknya Pada Keputusan Pembelian (Studi Pada Pengguna Iphone Mahasiswa Universitas 17 Agustus 1945 Jakarta) - Koerniawan Hidajat; Dini Diovana Koesumaningrum (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2021)
This study aims to determine the effect of word of mouth and brand image on purchasing decisions on iphone smartphones. This research was conducted on Apple iPhone smartphone users. The population in this study is the University Students August 17, 1945 Jakarta, people who use iphone smartphones and know the iPhone smartphone products. The technique used in this writing test uses purposive sampling technique, which is sampling technique with certain considerations. Data collection is done by providing a list of questions to respondents and tested using the SPSS data analysis method. Based on statistical tests, the results of the study showed that Word of Mouth directly had a positive and significant effect on purchasing decisions on product quality significantly affected purchasing decisions, while Brand Image directly had a negative and significant effect on purchasing decisions. There is a significant influence between Word of Mouth on purchasing decisions. And there is a significant influence between Brand Image on purchasing decisions.Keywords: Word of Mouth, Brand Image, Citra Merek, Keputusan Pembelian